New Species of Biting Midges in the Dasyhelea atlantis-bermudae Complex (Diptera: Ceratopogonidae) - Jr., William L. Grogan; Hribar, Lawrence J. (Zootaxa, 2025)
We provide a review of biting midges in the Dasyhelea atlantis-bermudae complex in the D. mutabilis group in the United States and Caribbean region. We also describe and include photomicrographs of D. atlantis Wirth & Williams, D. bermudae W. & W., three new species from Florida and a 4th new species from Jamaica. A key to adults in the D. atlantis-bermudae complex is provided as well as the first records of D. atlantis from Mexico and a new USA record from Maryland.